Thomas De Quincey between Romantics and Victorians - Céline Lochot (Cahiers Victoriens et Edouardiens)
Asserting himself as a scholar, De Quincey expresses both the need for an alter ego and the fear of losing his own identity as an author in the process. Longing for the past, unsure of his own value and status, he sees the emergence of Victorian modernity as a space where to define and lose himself; and is at his most creative when he manages to embrace the global uncertainty.